Analytical Rheology of Polymer Melts: State of the Art. (17th September 2012) - Shanbhag, Sachin
Abstract : The extreme sensitivity of rheology to the microstructure of polymer melts has prompted the development of "analytical rheology, " which seeks inferring the structure and composition of an unknown sample based on rheological measurements. Typically, this involves the inversion of a model, which may be mathematical, computational, or completely empirical. Despite the imperfect state of existing models, analytical rheology remains a practically useful enterprise. I review its successes and failures in inferring the molecular weight distribution of linear polymers and the branching content in branched polymers.